The Role of Religion in Shaping Knowledge and Identity in Amitav Ghosh’s The Calcutta Chromosome - Hiwrekar Laxman Anantrao, Dr. Rafique Khan (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2025)
Amitav Ghosh’s The Calcutta Chromosome presents a complex narrative that interlaces religion, myth, and science to challenge conventional understandings of knowledge and identity in a postcolonial context. This paper examines how religious beliefs and practices function not as peripheral cultural elements but as essential frameworks for interpreting reality, generating knowledge, and asserting agency. Through characters such as Mangala and Lutchman, the novel foregrounds indigenous spiritual traditions and mystical practices as valid epistemologies that resist the dominance of Western scientific rationalism. Religious motifs—drawn from Hinduism, Islam, and localized cultic rituals—are integrated into the plot as tools for historical re-interpretation, offering a counter-narrative to the colonial account of Ronald Ross’s malaria discovery. In doing so, Ghosh reimagines science not as an isolated, objective enterprise but as a culturally embedded process shaped by multiple belief systems. Religion in the novel also becomes a powerful site for identity formation, enabling marginalized characters to reclaim intellectual and historical agency. The interplay between cyclical mythic time and linear scientific chronology disrupts colonial historiography, positioning spiritual frameworks as equally credible avenues to truth. Ultimately, the novel proposes a syncretic model of knowledge production in which faith, culture, and science coexist, thereby redefining the boundaries of both identity and intellectual authority.